Analisis Hubungan Ketidakseimbangan Fiskal dan Tingkat Investasi terhadap Transaksi Berjalan di Indonesia, Periode 2000 Kuartal Pertama â 2012 Kuartal Kedua - , ANISHA WIRASTI C ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this study is to empirically examine the Twin Deficit Hypothesis and Feldstein-Horioka Hypothesis in Indonesia for the period 2000 quarter 1 until 2012 quarter 2. Bound Testing is applied to examine the cointegration relationship within model. The cointegration results show that fiscal imbalances and investment have a long run relationship on current account imbalances. Researcher applies Autoregressive Distributed Lag (ARDL) approach to estimate the long run relationship within model and applies Autoregressive Distributed Lag-Error Correction Model (ARDL-ECM) approach to estimate short run relationship within model. The estimation results show that the fiscal imbalances have a positive impact on the current account imbalances in Indonesia and investments have a negative impact on the current account. The value of investment coefficient is near to zero. Those results indicate that Twin Deficit Hypothesis and Feldstein-Horioka Hypothesis hold in Indonesia.